Assay Of Fungicides And Bioagents To Ascertain The Variability Among Isolates Ofcolletotrichum Capsici Inciting Of Chilli Fruit Rot (Journal of Plant Disease Sciences, 2020)
Ten isolates of Colletotrichum capsici collected from different regions of Vidarbha, Marathwada (Maharashtra), Bidar district (Karnataka) and Guntur district (Andra Pradesh) showing varied type of pathogenic ability against chilli variety Jayanti and designated as strongly, moderately and weakly pathogenic on the basis of per cent disease intensity. Sensitivity of fungicides against different isolates considered for assessment of variation as well as for management. Isolate Cc1 was highly sensitive to ridomil MZ and tricyclazole + mancozeb, while ridomil MZ, propiconazole, mancozeb and tricyclazole + mancozeb against Cc2, and propiconazole and tricyclazole + mancozeb to Cc3, whereas tricyclazole + mancozeb was inhibitory to Cc4 and Cc5. Tridemorph was showing cent per cent inhibition of Cc6 and propiconazole against Cc7, Cc8 and Cc10, while in Cc9 tridemorph, propiconazole and a combination of carbendazim + mancozeb were shown cent per cent inhibition. These observations reflect in the existence of variation among the isolates. However, the same fungicides exhibited inhibitory effect on spore germination of C. capsici isolates. A combination of tricyclazole + mancozeb @ 0.2 per cent and propiconazole @ 0.1 per cent showed cent per cent spore inhibition effect along with other chemicals against all the ten isolates of C. capsici. Among the bioagents Trichoderma harzianum was found to be significant in inhibiting the mycelial growth of Cc1, Cc2, Cc3, Cc5, Cc6, Cc8 and Cc10 isolates of C. capsici, while T. viride inhibit the growth of Cc4, Cc7 and Cc9, whereas Pseudomonas fluorescens was found to be moderate in reducing the growth of all the isolates of C. capsici.
Keywords: Colletotrichum; capsici; Fungicides; Bioagents; Chilli